Hak dan Kewajiban Suami Istri dalam Bersosial Media Perspektif Hukum Islam dan Feminisme - Deny Widiyanto, Arya; Jauhar Wicaksono, Firdaus (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2025)
The rights and obligations of husbands and wive’s particularly in relation to social media use can significantly affect household harmony. Poorly managed social media activity may trigger marital tension and even lead to infidelity, which undermines commitment within the family. This study aims to analyze the concepts of mubādalah and androgyny in the distribution of rights and obligations between spouses, as well as to address emerging challenges faced by married couples in the social media era. This research a qualitative method with a library research approach. The data sources include Faqihuddin Abdul Kodir Qira’ah Mubādalah, journals, books, and other relevant articles. The study examines how these two concepts function as ethical and practical frameworks for responding to domestic issues in the age of social media. The concept of mubādalah emphasizes mutuality, partnership, and gender justice in marital relations, while androgyny offers adaptive role flexibility, enabling spouses to move beyond rigid gender based role divisions. The integration of these concepts affirms that the rights and responsibilities of husbands and wive’s should be understood as shared duties that can be negotiated through deliberation and mutual trust.